Pelaksanaan Pembelajaran Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan Materi Kebugaran Jasmani di Smk Negeri 3 Batu - Neng Rina Rina; Ari Wibowo Kurniawan (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2023)
This study aims to determine the level of physical fitness of students at SMK Negeri 3 Batu and the implementation of PJOK learning at SMK Negeri 3 Batu. This research method uses a quantitative descriptive method using the TKJI test instrument to measure the level of physical fitness of students at SMK Negeri 3 Batu and non-test instruments in the form of a questionnaire used to measure the implementation of PJOK learning at SMK Negeri 3 Batu. The population in this study was 88 students of SMK Negeri 3 Batu and 3 PJOK teachers at SMK Negeri 3 Batu. The results of the data analysis showed that there were no male students who included very good criteria, for good criteria 1%, moderate criteria 59%, 37% less criteria, and 3% less criteria and for the overall results female students were not included in the criteria very good and good criteria, for moderate criteria 60%, less criteria 27% and for very poor criteria 3% and for the process of implementing PJOK learning at SMK Negeri 3 Batu in the learning process that learning aspects with a percentage level of 71% in giving motion assignments physical fitness percentage level as much as 80% and for learning evaluation with a percentage of 88%. The research concluded that the results of the physical fitness test for students at SMK Negeri 3 Batu, most of the students entered into the moderate category, and the process of implementing PJOK learning at SMK Negeri 3 Batu was included in the good category.